Iniciativas de Apropiación Social de la Ciencia y la Tecnología en Colombia: tendencias y retos para una comprensión más amplia de estas dinámicas Colombian initiatives in the Social Appropriation of Science and Technology: tendencies and challenges for a broader understanding of these dynamics - Tania Pérez-Bustos; Manuel Franco Avellaneda; Marcela Lozano Borda; Sigrid Falla; Diana Papagayo (História, Ciências, Saúde: Manguinhos)
Pretende ampliar la comprensión que en Colombia se ha tenido sobre la Apropiación Social de la Ciencia y la Tecnología (ASCyT), particularmente en lo que refiere al tipo de actores que promueven iniciativas en ese sentido. Apoyándose en una metodología de rastreo por vínculos, se identificaron y documentaron cien iniciativas de ASCyT en el país, promovidas desde la sociedad civil, el estado, la empresa, las comunidades de investigadores y los escenarios mediadores. El artículo analiza estas iniciativas y señala los desafíos que presentan para descolocar y volver más participativo el enfoque que se le ha dado a la ASCyT en el país. Is aimed at broadening Colombia's understanding of the social appropriation of science and technology, particularly the types of actors who promote initiatives in this sphere. Using a chain referral sampling methodology, a hundred such initiatives in Colombia were identified and documented, which were promoted by civil society, the State, business, the research community and mediators. The article further analyzes these iniciatives and indicates the challenges they represent, especially in breaking down the traditional approach to the social appropriation of science and technology in Colombia and replacing it with more participative strategies.